Facile deposition of NiFe-LDH ultrathin film on pyrolytic graphite sheet for oxygen evolution reaction in alkaline electrolyte. (15th February 2022) - Gozzo, Cipriano B.; Soares, Mario R.S.; Destro, Fabrício B.; Junior, João B.S.; Leite, Edson R.
Abstract: NiFe-layered doubly hydroxide (LDH) is one of the most active materials for hydroxyl oxidation in an alkaline electrolyte. In this study, we explored a facile method of depositing NiFe-LDH catalyst on pyrolytic graphite sheets (PGSs) to explore the synergistic effects at the substrate–electrocatalyst interface. The catalyst was electrodeposited on PGSs using chronoamperometry. The homogeneous distribution of the catalyst with nanosheet morphology on the PGS's surface produced an ultrathin film. The NiFe25/PGS sample showed a low overpotential (332 mV) and Tafel slope (33 mV dec −1 ). The fitting of the Nyquist plots was performed using an equivalent circuit, and the NiFe25/PGS (1.69 Ω) sample showed the lowest charge transfer resistance among the studied catalysts. In addition, PGS proved a better substrate for the alkaline oxygen evolution reaction compared to glassy carbon and fluorine-doped tin oxide. Graphical abstract: Image 1 Highlights: Facile deposition of NiFe25 on surface of PGS. NiFe25/PGS showed a nanosheet morphology. NiFe25/PGS was effective for oxygen evolution reaction (332 mV at 10 mA cm −2 ). PGS proved to be a better substrate for the alkaline OER in comparison of GC and FTO.